Extrabudgetary civil protection fund - Milić, Igor; Milić, Kristina; Vitas, Petar (Crisis Management Days, 2025)
Extrabudgetary funds represent a specific financing mechanism that enables the targeted collection and allocation of resources for specific purposes. The Civil Protection System Act of 2015 stipulated that the Republic of Croatia should establish an extrabudgetary civil protection fund through a special law to secure financial resources for protection and rescue in major emergencies and disasters. A special law was supposed to regulate the establishment and operation of the extrabudgetary civil protection fund, but this was never implemented. The extrabudgetary civil protection fund can play a key role in ensuring the security and resilience of the community in the face of extraordinary events that can escalate into major emergencies and disasters. The civil protection system in the Republic of Croatia encompasses a wide range of activities aimed at protecting people, property, and the environment from threats and risks. Financial resources are crucial for implementing these activities, and an extrabudgetary fund can provide an additional, stable and predictable source of financing, as well as supplement existing budgetary funds—which, at the local and regional self-government levels, are often insufficient for routine activities. Such funds enable rapid action, as the resources are immediately available for procuring essential equipment, mobilizing operational forces, and providing urgent assistance. The extrabudgetary civil protection fund can also offer support in the preparation and implementation of disaster risk reduction activities, as well as assist local government units in carrying out civil protection measures and activities within their jurisdiction. For the management of the fund to be sustainable and transparent, it is necessary to clearly define both the sources of financing and the decision-making process for the allocation of financial resources. In the prevention phase, financial resources may be made available through calls for proposals aimed at achieving specific objectives, while in the response phase they can support the implementation of priority civil protection measures based on decisions by the competent authorities within the civil protection system. This paper aims to demonstrate the importance, role, and challenges associated with managing the extrabudgetary civil protection fund. Through the conducted research, the paper will present financial indicators related to the planning and expenditure of funds from budgetary sources as well as international projects at the level of local and regional self-government units, to determine the priorities for the development of civil protection that can be financed through the extrabudgetary civil protection fund. The extrabudgetary civil protection fund can be a key tool in strengthening the community’s resilience against various threats and risks. Its effectiveness depends on transparent and accountable management, the assurance of stable sources of financing, and the cooperation of all relevant stakeholders and operational forces within the civil protection system. Through continuous improvement and adaptation, such a fund can significantly contribute to the safety and quality of life of citizens, as well as to the overall strengthening of the civil protection system in the Republic of Croatia.